(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The utilization of hybrid epoxy composites, reinforced with both banana and glass fibers, has gained significant attention in recent years. This study conducts a comprehensive exploration of the mechanical and crystallographic properties of such composites. The investigation includes an analysis of tensile strength and modulus, flexural strength and modulus, impact resistance, compression strength, fatigue properties, and statistical data analysis. Moreover, it delves into the correlation between mechanical and crystallographic properties, elucidates the synergistic effects between banana and glass fibers, and identifies critical factors influencing composite performance.